The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cimb43030153
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Gemcitabine and PBPK Modeling to Assess Oral Administration

Abstract: Gemcitabine is a nucleoside analog effective against several solid tumors. Standard treatment consists of an intravenous infusion over 30 min. This is an invasive, uncomfortable and often painful method, involving recurring visits to the hospital and costs associated with medical staff and equipment. Gemcitabine’s activity is significantly limited by numerous factors, including metabolic inactivation, rapid systemic clearance of gemcitabine and transporter deficiency-associated resistance. As such, there have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For instance, a gemcitabine PBPK model was developed using Gastroplus software with IV and oral routes of administration to evaluate the plasma-concentration time profile. The author showed that the drug Cmax was lower, but AUC (area under curve) was higher for the tablet dosage regimens (1000 mg, three/day and 1500 mg 2–3 times a day) compared to the IV infusion [ 47 ]. Often, the availability of the compound in systemic circulation is dependent on multiple factors.…”
Section: Unravelling the Art Of Developing Pbpk Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a gemcitabine PBPK model was developed using Gastroplus software with IV and oral routes of administration to evaluate the plasma-concentration time profile. The author showed that the drug Cmax was lower, but AUC (area under curve) was higher for the tablet dosage regimens (1000 mg, three/day and 1500 mg 2–3 times a day) compared to the IV infusion [ 47 ]. Often, the availability of the compound in systemic circulation is dependent on multiple factors.…”
Section: Unravelling the Art Of Developing Pbpk Modelsmentioning
confidence: 99%
“…The inhalation route is quite successful in respiratory diseases and also for rapid systemic drug delivery. A PBPK model was built for inhaled nemirasalib, consisting of extra-thoracic, thoracic, bronchiolar and alveolar tissues for evaluating pulmonary drug absorption [ 47 ]. For environmental chemical such as xylene, PBPK with lungs as a route for inhalation and exhalation was modeled for reconstructing the human exposure [ 52 ].…”
Section: Unravelling the Art Of Developing Pbpk Modelsmentioning
confidence: 99%
“…For instance, gemcitabine PBPK model was developed using Gastroplus software with IV and oral route of administration to evaluate plasma-concentration time profile. Author showed that the drug Cmax was lower, but AUC was higher for the tablet dosage regimens (1000 mg, three*/day and 1500 mg 2-3*/day) compared to the IV infusion (Ferreira et al, 2021) Often the availability of the compound in systemic circulation is dependent on multiple factors. For instance, absorption is often considered the critical parameter for oral route along with influence from fasting or fed state.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…Inhalation route of exposure is quite successful in respiratory diseases and also for rapid systemic drug delivery. PBPK model was built for inhaled nemirasalib consisting of extra-thoracic, thoracic, bronchiolar and alveolar tissues for evaluating pulmonary drug absorption (Ferreira et al, 2021). For environmental chemical like xylene, PBPK with lungs as a route for inhalation and exhalation was modeled for reconstructing the human exposure (McNally et al, 2012).…”
Section: Route Of Administrationmentioning
confidence: 99%
“…The generic GastroPlus ® ACAT model provided reasonable predictions especially for biopharmaceutical classification system (BCS) class 1 compounds [20]. In addition, the ability of PBPK models to predict oral PK will also improve, providing a better tool for the discovery and development of new medicines [21][22][23][24], as drug combinations or drug synergism.…”
Section: Introductionmentioning
confidence: 99%